2020
DOI: 10.1186/s12876-020-01385-x
|View full text |Cite|
|
Sign up to set email alerts
|

Cystinosis beyond kidneys: gastrointestinal system and muscle involvement

Abstract: Background: Cystinosis is a multisystemic disease resulting from cystine accumulation primarily in kidney and many other tissues. We intended to study the evolution of less commonly seen extrarenal complications of cystinosis in a group of patients who have periods without cysteamine treatment. Methods: Gastrointestinal and muscular complications of cystinosis were studied in a group of 21 patients. Results: Twenty one patients were included in the study. Among them, 14 were homozygous and 3 were compound hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Among the remaining patients studied, the most common gastrointestinal complication was nausea and abdominal pain, which was more common among patients who were diagnosed later. According to Topaloglu et al, a study performed on patients with cystinosis revealed that the mean age at last visit was 11.3 ± 6.5 years, and that complications, such as hepatomegaly, swallowing difficulty, and portal hypertension, were found ( 15 ). Two previous studies were performed on patients who did not take cystagon regularly, and this may make the result different from our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the remaining patients studied, the most common gastrointestinal complication was nausea and abdominal pain, which was more common among patients who were diagnosed later. According to Topaloglu et al, a study performed on patients with cystinosis revealed that the mean age at last visit was 11.3 ± 6.5 years, and that complications, such as hepatomegaly, swallowing difficulty, and portal hypertension, were found ( 15 ). Two previous studies were performed on patients who did not take cystagon regularly, and this may make the result different from our study.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Rizantoploglober et al on these patients revealed that even in childhood, in addition to renal dysfunctions, extrarenal organs might be involved by cystine accumulation, especially in patients who are incompliant to treatment. This can result in complications such as swallowing difficulties, hepatomegaly, and portal hypertension ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that the author name Ayşe Gültekingil was incorrectly written as Ayşe Gültekingil Keser. The original article [ 1 ] has been updated.…”
Section: Correction To: Bmc Gastroenterology (2020) 20:242 101186/s12...mentioning
confidence: 99%
“…There are many extrarenal complications which accompany INC and strongly impact a patient's quality of life: Ophthalmological manifestations can affect every part of the eye—an early and frequent symptom is photophobia due to corneal crystal deposition ( 17 ). Gastrointestinal symptoms of INC are caused by cysteamine treatment and/or by cystine deposition in the gut wall ( 18 ). The most common endocrinological complications of the disease are hypothyroidism, diabetes mellitus ( 1 ), pubertal delay ( 19 , 20 ), and male infertility ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most common endocrinological complications of the disease are hypothyroidism, diabetes mellitus ( 1 ), pubertal delay ( 19 , 20 ), and male infertility ( 21 ). Muscle impairment is not only of concern for bone metabolism and strength, but may lead to swallowing difficulties and respiratory insufficiency ( 16 , 18 ). Short stature, skeletal pain and deformities, as well as a higher risk of fractures are more common in INC and growth also seems to follow a different pattern than in other nosologic entities of chronic kidney disease (CKD) ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%